SISTEM PEMANTAU DISTRIBUSI SURAT KABAR MENGGUNAKAN JARINGAN SELULER DAN INTERNET (Studi Kasus : PT Joglosemar Prima Media Surakarta) - , I Putu Suhada Agung, ST; , Ir. P. Insap Santosa, M. Sc., Ph. D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In the press industry requires the distribution process for the newspaper market, which involves the operational manager and transport division to agents in a number of areas. Agent sends the report in the form of SMS. Operational manager validate and recap reports in printed form. In this way, the management had difficulty in monitoring the distribution of newspapers. Newspapers Distribution Monitoring System utilizes SMS data is used as input and location data on a map of the distribution status. It should be made filters to distinguish normal SMS with SMS formatted. Data filters compared to the XML data that contains information agents coordinate location data. Maps are displayed using XML data. XML format via asynchronous JavaScript is used as an intermediary between the database and Google Maps. Monitoring the distribution of newspapers can be done by viewing a map with a marker (to determine position) and the info window (containing the information agent, location, number of copies and delivery time).